Replication of Atwood's (2022) "The Long-Term Effects of Measles Vaccination on Earnings and Employment" - Mara Barschkett; Mathias Huebener; Andreas Leibing; Jan Marcus; Shushanik Margaryan (Institute for Replication (I4R), 2023)
Atwood (2022) analyzes the effects of the 1963 U.S. measles vaccination on longrun labor market outcomes, using a generalized difference-in-differences approach. We reproduce the results of this paper and perform a battery of robustness checks. Overall, we confirm that the measles vaccination had positive labor market effects. While the negative effect on the likelihood of living in poverty and the positive effect on the probability of being employed are very robust across the different specifications, the headline estimate-the effect on earnings-is more sensitive to the exclusion of certain regions and survey years.
Keywords: 330